Isolation and Identification of Microorganisms from Mobile Phones of staff and students of Yusuf Maitama Sule University, Kano - Ruqayyah Hamidu , Muhammad; Hauwa Yunusa, Sarina (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Mobile phones act as fomites turning these devices into ideal platforms for disease transmission either by means of self-inoculation when touching your own mobile phone and face or by simple microbial dissemination in the environment, public places, or professional sectors. The mobile phones of both staff and students were collected and swabbed using aseptic techniques. Nutrient agar and Potato dextrose agar were prepared according to manufacturer’s instructions, for culturing bacteria and fungi respectively. The swabs were streaked on the solidified media and incubated in an inverted position at 37oC for 24 hours for bacteria and 48-72 hours for fungal growth. Morphological description of colonies, gram stain mobility tests and identification keys were used for bacterial identification. Physiological and biochemical reactions of each bacterial isolate were verified using the standard kits API identification system (Biomerieux, Marcy L’etoil, France) for the identification of both gram positive and negative bacteria. Fungal colonies were studied macroscopically by observing the colony features (colour, shape, size and hyphae) and microscopically using a compound microscope with a digital camera using a lactophenol cotton blue- stain slide. Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Proteus mirabilis, Bacillus subtilis and Enterobacter aerogenes were the obtained bacterial isolates, while Aspergillus niger, Cladosporium spp, Penicillium spp, Rhizopus stolonifer and Aspergillus fumigates were the fungal isolates. The study showed that the mobile phones were found contaminated with both bacterial and fungal microorganisms, some of which are indicators of feacal contaminants. There is the need for further studies to determine the survival time of pathogens on cell phones. Also, there is need for water system rest rooms for both students and staff in the city campus to improve hygiene. The importance of constant hand wash and decontaminating the phones using 70% alcohol cannot be over emphasized.